Patients' views and experiences on the use and safety of directly acting oral anticoagulants: a qualitative study - Abdulrhman Al Rowily; Mohamed A. Baraka; Mohammed H. Abutaleb; Aliah M. Alhayyan; Nouf Aloudah; Zahraa Jalal; Vibhu Paudyal (Taylor & Francis Group, 2023)
Abstract Background Direct oral anticoagulants (DOACs) are considered high-risk medications and used to prevent thromboembolic events and stroke. This study aimed to examine patients' views and experiences of DOACs use and factors that can promote safety associated with DOACs. Methods In-depth interviews were conducted with adult patients who had been prescribed DOACs, identified and invited by local collaborators in three different tertiary care hospitals in Saudi Arabia. A topic guide developed based on was used to inform the interview. Data were analysed thematically. Results Data saturation was achieved by the ninth participants. Three major themes were identified: (1) factors affecting DOAC's safety from the patients view; (2) barriers to adherence to DOACs and (3) strategies to promote the safety of DOACs. Lack of knowledge of DOACs, using inappropriate sources of information, lack of communication with HCPs, difficulty in having access to DOACs and lack of monitoring were the main factors affecting the safe use of DOACs. Unavailability of the drugs and difficulty in timely getting to hospitals affected adherence. Patients acknowledged difficulties communicating with healthcare professionals, timely access to anticoagulation clinics and in obtaining their DOACs on time. Conclusions There is a need to develop and evaluate theory-based interventions to promote patient knowledge, understanding and shared decision-making to optimise DOACs use and improve their safety.